Effect of adding tyndallized probiotics to the World Health Organization standard therapy for acute diarrhea in children - Kesatrianita Mawarni Fanny; Wahyu Damayanti; Mohammad Juffrie (Paediatrica Indonesiana, 2012)
Background Diarrhea is the major cause of morbidity and mortalityin children. Probiotics can decrease the frequency and durationof diarrhea. There are two types of probiotics, live and tyndallized.Tyndallized probiotics have been stetilized, so they are unable to produceactive metabolites, but may have an effect on human immunity.Objective To evaluate the effectiveness of supplementing WHOstandard therapy with tyndallized probiotics in children withacute, watery diarrhea.Methods We performed a randomized, single-blind, controlledtrial in children aged 3-60 months who were diagnosed with acute,watery diarrhea at Gunungsitoh General Hospital, Nias, NorthSumatera. Subjects were collected by consecutive sampling byway of parent interviews.Results One hundred subjects with acute, watery diarrhea weredivided into 2 groups of 50. One group was treated with onlyWHO standard therapy for acute, watery diarrhea. The othergroup was treated by WHO standard therapy with the additionof tyndallized probiotics. There were no significant differences inbasic characteristics between the two groups. Diarrheal durationfor the group receiving WHO standard therapy only was 3.95 ±1.3 days, while that of the group receiving both WHO standardtherapy and tyndallized probiotics was 4.6 ± 2.3 days (P > 0.05).Diarrheal frequency on the fifth day in the WHO standard therapygroup was 1.90 ± 0.99 times per day, while that of the tyndalhzedprobiotic group was 1.56 ± 0.67 times per day (P > 0.05).Conclusion There were no significant differences between WHOstandard therapy alone and WHO standard therapy with the additionof tyndallized probiotics for decreasing the duration and frequency ofdiarrhea in children. [Paediatr lndones. 2012;52:91-4].